Retreatment of a 6-Canalled Mandibular First Molar with Four Mesial Canals: A Case Report - Mohsen Aminsobhani; Noushin Shokouhinejad; Sholeh Ghabraei; Behnam Bolhari; Abdollah Ghorbanzadeh (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
Successful root canal treatment requires adequate knowledge regarding morphologic variations in root canal system of teeth. This report describes a six-canalled mandibular first molar with four mesial root canals requiring endodontic retreatment. The two additional canals in the mesial root were found during retreatment with the aid of illumination and magnification. In conclusion, the possibility of atypical morphology and additional canals should never be over looked.